2021
DOI: 10.3390/vaccines9030239
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of HIV-1-Based Virus-Like Particles with Increased Incorporation and Stability of Membrane-Bound Env

Abstract: An optimal prophylactic vaccine to prevent human immunodeficiency virus (HIV-1) transmission should elicit protective antibody responses against the HIV-1 envelope glycoprotein (Env). Replication-incompetent HIV-1 virus-like particles (VLPs) offer the opportunity to present virion-associated Env with a native-like structure during vaccination that closely resembles that encountered on infectious virus. Here, we optimized the incorporation of Env into previously designed mature-form VLPs (mVLPs) and assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 130 publications
0
10
0
Order By: Relevance
“…This conformational diversity also imposes significant barriers in the development of efficient vaccines aimed to induce broadly neutralizing antibodies, and several strategies have been proposed to stabilize Env trimers in the pre-fusion state (58)(59)(60)(61). Recently, Gonelli et al (62) generated VLPs displaying stabilized HIV Env trimers by introducing inter-subunit disulfides and a proline substitution (SOSIP) mutation. The resulting modified VLPs can efficiently activate B cells by displaying epitopes recognized by broadly neutralizing antibodies while minimizing exposure of nonneutralizing antibody sites (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conformational diversity also imposes significant barriers in the development of efficient vaccines aimed to induce broadly neutralizing antibodies, and several strategies have been proposed to stabilize Env trimers in the pre-fusion state (58)(59)(60)(61). Recently, Gonelli et al (62) generated VLPs displaying stabilized HIV Env trimers by introducing inter-subunit disulfides and a proline substitution (SOSIP) mutation. The resulting modified VLPs can efficiently activate B cells by displaying epitopes recognized by broadly neutralizing antibodies while minimizing exposure of nonneutralizing antibody sites (62).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gonelli et al (62) generated VLPs displaying stabilized HIV Env trimers by introducing inter-subunit disulfides and a proline substitution (SOSIP) mutation. The resulting modified VLPs can efficiently activate B cells by displaying epitopes recognized by broadly neutralizing antibodies while minimizing exposure of nonneutralizing antibody sites (62).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, VLPs with increased incorporation and stability of membrane-bound HIV-Env demonstrated superior immunogenicity than wild-type VLPs in mice 53 . Indeed, VLPs with increased density of Env are currently being pursued for vaccine development 55 , 56 . In our study we demonstrated that an IDLV expressing a membrane bound ConSOSL.UFO.750 induced higher IgG titers than an IDLV expressing the soluble ConSOSL.UFO.664, suggesting that expression of membrane-tethered Env trimers by IDLV is superior at activating B cells and inducing antigen specific antibodies compared to IDLV expressing soluble trimers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increasing the native-like Env trimer density on the surface of IDLV particles has the potential to increase Env recognition by immune cells and therefore results in more potent immune responses 51,52 . Indeed, VLPs with increased density of Env are currently being pursued for vaccine development 53,54 . By displaying viral antigens on a viral surface, VLPvaccines are strong inducers of Abs and helper T cell responses 55 .…”
Section: It Has Been Shown That Muscle Cells Can Produce Envs Exposing Quaternary-dependentmentioning
confidence: 99%